Associations between Health and Academic Success at a Florida University: An Exploratory Cross-sectional Study - Jessica Weissman; Sharice Preston; Elena Sebekos; Willmarie Latorre; Bandar Alsaif; Karl Krupp; William Darrow (University of North Florida, 2016)
The aims of the study were to explore the associations between college students' perception of their overall physical and psychological health and four measures of academic performance. College students (N = 265) completed a 65-item Web-based survey in a university's student health services building during the spring 2015 semester. Poorer psychological health was associated with seriously considering dropping out of college and missing more classes during the current school year "due to physical or psychological health reasons." Poorer physical health was associated with enrollment in more credit hours. Students who reported a grade point average (GPA) below 2.0 missed more classes "because of physical or psychological reasons" during the current school year than those with a 2.0 or higher GPA. A longitudinal study is needed to clarify whether better health leads to more successful academic performance or vice versa and which specific health indicators play the largest role.